As mudanças do setor sucroenergético de Alagoas sob a perspectiva dos motores de transformação - Chen, Tony Xu Taur (2017)
Objective: Identify and explain the main recent transformations of the production and innovation system of the sugar-energy sector in Alagoas through the sector transformation engines. Method: In the present work, a combined methodology was applied: the Delphi method and the content analysis method. The Delphi method was used to perform data collection and the content analysis method for data processing and analysis. Theoretical reference: In the theoretical reference have the approach and the treatment on the evolutionary theory, involving concepts of Innovation System, industrial transformation, coevolution, Sectorial System of Innovation, Functions of the System of Innovation and engines of transformation. Results: The results obtained in this work were four transformation engines: (1) development of sugarcane varieties, (2) period of high sugar prices in the international market and the 2004-2006 flex-fuel car season, (3) closing of companies and mills from 2015, (4) agricultural and industrial technologies. Each engine has its own set of Functions of the Innovation System, which explain how certain events have generated structural transformations within the Alagoas sugar-energy sector and what their effects are. Contributions and limitations: This work sought to contribute to the knowledge of the combined methodology, Delphi and content analysis, for applications in national works, considering that the combination of these methodologies is more found in works abroad. Among some limitations of this work are the lack of assurance on the forecasts made and the lack of certainty in the impartiality of the interviewees in the interviews.